Investigating determinants of innovation performance maturity in Malaysian private universities: A partial least squares structural equation modelling analysis - Ainin Zakiah, Othman; Nur Balqishanis, Zainal Abidin (EDP Sciences, 2024)
In response to the dynamic changes in the contemporary world, innovation has become imperative for Private Higher Education Institutions (HEIs) to keep pace with evolving institutions. While Total Quality Management (TQM) practices have been extensively examined in the context of determining factors supporting innovation performance, conflicting results from various studies necessitate a fresh perspective. This study adopts the Capability Maturity Model (CMM) to enhance the impact of TQM practices on Innovation Performance, introducing a novel hybrid theory termed TQM-CMM which is a combination of TQM and CMM to enhance the application of TQM practices by assessing its maturity level, addressing the issue of conflicting results observed in previous studies. The objective is to elucidate the interconnected relationships among key factors influencing innovation performance in private higher education institutions (HEIs). A survey conducted at Malaysian private HEIs, yielding 115 valid responses, reveals that two out of seven hypothesized correlates among the constructs were statistically significant at two-tailed tests, evidenced by t values exceeding 1.96 calculated from 10,000 bootstrapped samples. This research contributes valuable insights for academics and offers potential enhancements to university performance.